Sejarah Pembaruan Islam di Indonesia - Ananda, Rifki Abror; Fata, Ahmad Khoirul (Universitas Islam Negeri Raden Intan Lampung, 2019)
Islam is considered to be the religion that is most ready to face modernity. There are a number of values in this religion that can be the basis for people to enter in modern times. However, the process of modernization of Muslim societies is not without obstacles. Modernity that came from the West became a challenge in itself. Another challenge comes from within Muslims. In an effort to respond to all the challenges, a number of figures and reform movements emerged in the Islamic world. No exception in Indonesia. This paper provides an overview of the history of Islamic reform in Indonesia in the modern era. Namely in the 18th century, 19, until 20. During that time the renewal occurred with different themes. Also with different figures. However, these reforms also cover much of the life space of Muslims, ranging from social, religious, to political.